2012
DOI: 10.1038/oby.2011.325
|View full text |Cite
|
Sign up to set email alerts
|

FTO Risk Haplotype Among Early Onset and Severe Obesity Cases in a Population of Western Spain

Abstract: The strongest risk factor for childhood and adolescent obesity is parental obesity, and studies show that the strong predictive value of parental BMI results mainly from genetic rather than environmental factors (1,2). Therefore, the study of obese subjects from families with a high occurrence of obesity might reflect a stronger heritable component and prove helpful to increase the potential for detecting genetic associations. Several genome-wide association studies in European populations have identified that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…Despite the similar genetic background between European populations, it is known that for several polymorphisms, frequencies can vary within different Caucasian populations [23], [24]. Moreover, a few studies failed to associate some FTO polymorphisms and obesity [25], [26], highlighting the need of more studies in different populations to better understand the role of FTO gene in obesity. The present study is the first to test whether common FTO gene SNPs are associated with obesity or to related anthropometric traits in children of Portuguese origin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the similar genetic background between European populations, it is known that for several polymorphisms, frequencies can vary within different Caucasian populations [23], [24]. Moreover, a few studies failed to associate some FTO polymorphisms and obesity [25], [26], highlighting the need of more studies in different populations to better understand the role of FTO gene in obesity. The present study is the first to test whether common FTO gene SNPs are associated with obesity or to related anthropometric traits in children of Portuguese origin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have shown that the degree of LD in a population with African ancestry is lower than that in European populations (32). Recent studies have reported that the genetic variability in the FTO gene that is in high LD are associated with a risk of obesity in Spanish (33) and African Americans (27). Our study showed novel patterns of LD in the FTO gene ancestry of Malaysian Malays.…”
Section: Discussionmentioning
confidence: 99%
“…One-hundred and seventy severely obese since childhood patients were selected from families screened as part of a study to detect cases of morbid obesity in Extremadura (western Spain; González et al, 2012) and whose pathogenesis can be attributed primarily to genetic alterations. All of them reached a weight greater than +3SD before 14 years of age; their overweight had been maintained and they exposed at least two other morbid obesity cases among first-or seconddegree relatives.…”
Section: Patientsmentioning
confidence: 99%